Pre-operative Spermatic Cord Ultrasonography Helps to Reduce the Incidence of Metachronous Inguinal Hernia in Boys - Huang, Shoujiang; Yang, Xiuzhen; Li, Canping; Qian, Yunzhong; Zhao, Zhengyan; Liang, Jianfeng (Frontiers in Pediatrics, 2018)
Background/purpose: Thickening of the spermatic cord is a clinical sign of an inguinal hernia. We therefore tested whether pre-operative spermatic cord ultrasonography could reduce the incidence of metachronous inguinal hernia (MIH). Methods: Boys under 2 years old with an initial unilateral inguinal hernia were enrolled in this study. In whom the width of the asymptomatic-sided spermatic cord was ≥0.5 cm, these patients underwent contralateral groin exploration. Age at initial operation, weight, initial operation side, The the sonographic width of the spermatic cord, the operative findings and presence of MIH were recorded, and the relationship among them was studied. Boys in the US group underwent an open herniorrhaphy with pre-operative ultrasound examination; the non-US group included boys who did not undergo a pre-operative ultrasound examination. A receiver operator curve (ROC) analysis was performed to evaluated predictive value of the sonographic width of the spermatic cord for contralateral hernia. Results: A total of 24 months’ follow-up data were obtained from 1793 boys (US group 1162, non-US group 631). In the US group, the width of the hernia-sided spermatic cord (0.76±0.18 cm) was larger than the normal side (0.38±0.06 cm, P=0.001). And the width of nomal side spermatic cord had no significant difference between the groups regarding other factors such as age and weight. In whom the width of the asymptomatic-sided spermatic cord was≥0.5 cm, the corresponding incidence of CIH was 86.4% (57/66). The width of the spermatic cord predicted the presence of contralateral hernia with ROC area under the curve = 0.943 (95% CI=0.919-0.966). The total incidence of MIH was 4.1% (74/1793). The incidence of MIH in the US group was 2.2% (25/1162) much lower than 7.8% (49/631) in the non-US group (P<0.001). If the width of the asymptomatic-sided spermatic cord was 0.5cm and 0.54cm, the corresponding sensitivity was 0.682 and 0.294 respectively, the corresponding specificity was 0.991 and 1.000 respectively. Conclusion: If the width of the asymptomatic-sided spermatic cord of boys with initial unilateral inguinal hernia sonographic width was ≥0.5 cm, contralateral groin exploration was recommended, and it help to reduce the incidence of MIH.